Hyponatremia as a Predicting Factor of Mortality in Chronic Liver Disease (Medical Forum Monthly, 2024)
Objective: To determine the worth of hyponatremia as a predicting factor of poor prognosis and mortality in chronic liver disease.Study Design: Cross Sectional StudyPlace and Duration of Study: This study was conducted at the Department of General Medicine, Primary and Secondary Healthcare DHQ Hospital Narowal from January 2017 to January 2018.Materials and Methods: A total 192 patients were included in our study. All the patients who were suffering from chronic kidney disease, congestive cardiac failure, already using diuretic drugs and conivaptan/tolvaptan, and on dialysis were excluded from our study. The continuous data including age, MELD score, MELD -Na score, albumin, creatinine, alanine transaminase, aspartate transaminase, gamma glutamyltransferase, total bilirubin level, serum chloride, platelet count, international normalized ratio were analyzed by applying Student T test. All the nominal data including male percentage, etiology of the end stage liver disease and complications of cirrhosis were compared by applying Pearson Chi-square test. SPSS v.23 software used and a P value of <0.05 was considered significant.Results: Serum levels of alanine and aspartate transaminases (ALT & AST), gamma glutamyltransferase (GGT), total bilirubin and international normalized ratio (INR) was significantly low in the patients with serum sodium levels of ≥139mEq/L (p-value 0.014, <0.001, <0.001, 0.001 and 0.018, respectively) but serum chloride was significantly higher (<0.001) in this group.Conclusion: This study concludes that the concentration of sodium in the serum < 139 mEq/L combined with MELD- Na score more than 12 can be the extrapolative indicators of poor prognosis and mortality in the patients having chronic liver disease. This can be used to identify the threat of poor outcomes and adequate treatment can be given to improve the serum sodium levels and in turn, improve the prognosis